(3TQM bUjOI GdCdZGRs - (3eMeO GdNVQ Hf MHjHs ((3eMeO YHO Gddg Hf eMeO ehdhO s)
(3ChdgG (B:s
(3CeG HYO , abO SCdfi ef RQYJ dg ai bdHi GdeMHI , aCfHJJ SHY SfGHd GdYGde GdeMbb Yf ef GdeSGFd heG GdeSDhd HC(B'(3de ef GdSGFd s
(3BNQgG (B:s
(3hef jYJQV hGdYde Yfg jeYRd jQi GdfbU ai Yjf GdceGd hdG jOQ EfJgJ bUjOI GdYGde hCLhHJg dgG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs